A CORRUPTION FREE SOCIETY: A New Way of God’s Reign in Our Midst - A Alangaram (Asian Horizons, 2012)
Often people take it for granted and say, “Oh! Corruption is present everywhere.” But to know and understand this phenomenon, we need the support of certain scientific studies and reliable reports and news. In 2011, in the scale of world corruption, India is ranked 95 out of 178 countries. Such information speaks volumes about the corruption in India. Yes, corruption is a great road block to the development and growth of India today. It has enveloped almost all the structures of the Indian nation, namely, political, social, economic, cultural, educational, health, and military, making the criminals and the rich richer and the poor poorer.